Parameterization Proposal to Determine the Feasibility of Geographic Areas for the Green Hydrogen Industry Under Socio-Environmental and Technical Constraints in Chile - Serafini, D; Garrido-Lazo, R; Rodriguez-Machuca, P (Elsevier Ltd, 2024)
Chile, abundant in solar and wind energy resources, presents significant potential for the production of green hydrogen, a promising renewable energy vector. However, realizing this potential requires an understanding of the most suitable locations for the installation of green hydrogen industries. This study proposes a quantitative methodology that identifies and ranks potential public lands for industrial use, based on a range of technical parameters (such as solar and wind availability) and socio-environmental considerations (including land use restrictions and population density). The results reveal optimal locations that can facilitate informed, sustainable decision-making for large-scale green hydrogen implementation in Chile. While this methodology does not replace project-specific technical or environmental impact studies, it provides a flexible, general classification to guide initial site selection. Notably, this approach can be applied to other regions worldwide with abundant solar and wind resources, such as Australia and Northern Africa, promoting more effective and sustainable global decision-making for green hydrogen production. © 2023 The Author(s)